Teacher training through constructivist curriculum improvement: the case of an online programme for Turkish language teachers in the Republic of Cyprus - Antoniou, Katerina (Language Center, Cyprus University of Technology, 2021)
Training is a set of systematic procedures aimed at providing participants with knowledge, skills, abilities, or attitudes to improve their job performance within a specified period (Martin, Kolomitro & Lam, 2014; Richard & Farell, 2005). This case study aimed to fill some of the gap in the literature in the field of Teaching Turkish as a Foreign Language (TTFL) and more specifically that of Turkish language teachers' training (TLTT) (Yıldız, 2013; Şengül, 2015). This dissertation investigated Turkish language teachers’ practices working in the Republic of Cyprus (RoC) and established awareness of their major limitations which comprise the lack of teacher training during their undergraduate studies and the traditional training they receive indirectly from the traditional prescribed textbooks they use. Based on these results, an online teacher training programme was developed and implemented to train participants in TLTT, based on the learning theory of constructivism. This case study examined previous studies in the area of Turkish Language Teacher Training and aimed to a) identify TLTs’ current practices in Cyprus, b) develop and implement an online constructivist training programme for TLTs, c) guide participants to improve their teaching practices based on constructivism and d) evaluate the extent to which this was effective. Both qualitative and quantitative methods were used to collect data. This study addresses the need for more TLTT opportunities that will eventually improve the quality of TTFL.
Keywords: Teaching Turkish as a Foreign Language (TTFL); Τeacher training; Curriculum improvement; Online teacher training; Constructivism; Computer Assisted Language Learning (CALL); Textbooks; Turkish language teachers (TLTs); Turkish Language Teacher Training (TLTT)